Design guide for steel at elevated temperatures and high strain rates (Steel Construction Institute, 2001)
'High strength steel is often used on offshore structures where there is a risk of accidental fire and blast loads. Design for fire requires knowledge of elevated temperature data while design for blast loads requires knowledge of high strain rate material data. This document provides guidance on elevated temperature and high strain rate material property data that is currently available for high strength steels used specifically for offshore structures. The guidance covers the data required to carry out both simplified design checks and advanced nonlinear analyses."--Knovel.
"FABIG Technical Note 6 - September 2001."
At head of title: Technical note and worked examples to supplement the Interim guidance notes for the design and protection of topside structures against explosion and fire.
Keywords: Steel, High strength -- Effect of high temperature on.; Steel, High strength -- Effect of explosion on.; Blast effect.; Offshore structures -- Design and construction.; Offshore structures -- Fires and fire prevention.; Drilling platforms -- Design and construction.; Drilling platforms -- Fires and fire prevention.; elektronické knihy; electronic books